Exhaust Emissions of a Diesel Engine Operating by Biodiesel Fuel - Ilkilic, C. (Taylor & Francis Inc, 2009)
In this study, an alternative diesel fuel, of which chemical modification was made by transesterification with short chain methyl alcohols, was produced from sunflower oil. The modified products were then evaluated according to their fuel properties as compared to diesel fuel. The fuel properties considered were viscosity, pour point, calorific value, flashpoint, and cetane number in addition to some other properties. The effects of biodiesel and diesel fuel on a direct injected, four stroke, single cylinder diesel engine exhaust emissions were studied. The results showed on the emissions of the engine that there were about 30% reduction in CO, about 26% reduction in CO2, and about 25% reduction in NOx. The reduction exhaust emissions made the biodiesel a suitable alternative fuel for diesel engine and could help in controlling air pollution.
Keywords: alternative fuel; biodiesel fuel; diesel engine; emissions